The Effects of the 2008 Labour-Migration Reform in Sweden: An Analysis of Income - Nahikari Irastorza; Henrik Emilsson (Global Labor Organization (GLO), 2020)
In 2008, Sweden changed its labour-migration policy in order to facilitate more labour migration from countries outside the EU. The unique design of the new law meant abandoning most state ambitions to shape labour migration. Under the new regulation, there are no labour-market tests or any consideration of the level of human capital. Instead, policy-makers trusted employers to select workers. We adopt a difference-in-differences approach and apply a series of OLS regressions on register data to assess the effects of the policy change on non-EU labour migrants' labour-market outcomes, as measured by income. The effects of the policy change are substantial. Non-EU labour migration increased and its composition changed after the reform, resulting in a significant decrease in mean incomes. The regression analysis shows that, despite the favourable economic cycle during the post-reform period, moving to Sweden as a third-country labour migrant following the 2008 labour-migration reform had a negative effect on the migrants' annual income. However, this effect became marginal after controlling for occupational level. We conclude that changes in their occupational composition were the main drivers of the income drop for non-EU labour migrants. In sum, the new non-selective labour-migration policy lowered labour migrants' mean income by opening the door to unskilled labour.
Keywords: J15; J21; J30; J61; 330; Migration policy; effects; 2008 reform; labour migration; income; Sweden